Epidemiology and Outcomes of Clostridium difficile Infection in Hospitalized Patients within the US Military Health Care System. (4th October 2017) - Eberly, Matthew; Susi, Apryl; Rajnik, Michael; Adams, Daniel; Nylund, Cade
Abstract: Background: Clostridium difficile infection (CDI) has become an emerging epidemic in the healthcare community. Our study aims to characterize the epidemiology and measure the attributable cost, length of stay, and in-hospital mortality of CDI among hospitalized patients in the US military health system (MHS). Methods: We performed a retrospective cohort study of patients with CDI using MHS database billing records. Cases included all active duty patients, their dependents, or retirees admitted to a US military treatment facility for ≥2 days from October 2008 to September 2015 with a stool sample positive for Clostridium difficile via enzyme immunoassay, tissue cytotoxin assay, toxigenic culture, or polymerase chain reaction (PCR). Patient case-mix adjusted outcomes including in-hospital mortality, length of stay, and hospitalization cost were evaluated by high-dimensional propensity score adjusted logistic regression. Results: Among 1, 156, 672 admissions within the MHS from 2008–2015, we identified 1, 640 (0.14%) patients with CDI and found a significant increase in the trend of CDI over the 7-year study period ( P < 0.001). Median age (IQR) was 63 (41–76) in the CDI hospitalized group and 26 (6–46) in the non-CDI hospitalized group. Male gender was a risk factor for CDI (unadjusted odds ratio, 1.94; 95% confidence interval 1.76–2.14) and the majority of patients (84.5%) were associated with large-size medical centers. Patients hospitalized with CDI had significantly higher hospitalization cost (attributable difference [AD] 51, 959, P < 0.001), prolonged hospital stay (AD 11.8 days, P < 0.001), and in-hospital mortality (case-mix adjusted odds ratio 3.28; 95% confidence interval 2.69–4.00). Conclusion: CDI in hospitalized patients within the MHS is associated with advanced age, large medical centers, and an increased length of stay, hospital cost, and in-hospital mortality. We identified a significantly increased burden of hospitalization among patients admitted with CDI, highlighting the importance of infection control and antimicrobial stewardship initiatives aimed at decreasing the spread of this pathogen. Disclosures: All authors: No reported disclosures.